PERBANDINGAN STRATEGI MANAJEMEN HOTEL BERBINTANG DI BALI MENGHADAPI COVID-19 - I Made Budiasa; I Wayan Jendra; I Wayan Nurjaya (Universitas Triatma Mulya, 2021)
The aim of this research is to identify the management strategy done by star hotels in Bali in dealing with pandemi situation of Covid 19. It is descriptive qualitative research with virtual interview techniques and literature review. The reseach found out some similarities and differences held by star hotel management in facing the covid 19 situatioan. Both The Westin Resort Nusa Dua and Wyndham Garden Kuta Beach Bali apply the hotel management internal strategy carried out in facing the pandemi situation. They also implement efficiency and effectiveness in order to survive. These hotels are different in generic strategy. The Westin Resort Nusa Dua uses generic strategy based on Poster theory (1985), and functional strategy. Meanwhile Wyndham Garden Kuta Beach uses a Strategic Recovery Plan which inspired by the theory of Business Continuity or Disaster Recovery Plan that consists of 6 phases and 3 strategy steps to ensure the plan is implemented properly.